Assessing insect herbivory on broadleaf canopy trees at 19 natural forest sites across Japan. Issue 3 (25th March 2021) - Takafumi, Hino; Kanno, Yuri; Abe, Shin; Abe, Tetsuto; Enoki, Tsutomu; Hirao, Toshihide; Hiura, Tsutom; Hoshizaki, Kazuhiko; Ida, Hideyuki; Ishida, Ken; Maki, Masayuki; Masaki, Takashi; et al.
Abstract: We present the largest freely available herbivory dataset for Japan representing data collected from a network of 19 natural forest sites across the country. Sampled network sites were part of the Monitoring Sites 1000 Project organized by the Ministry of the Environment. Sites were located across a range of climate zones, from subarctic to subtropical, and broadleaf trees (both evergreen and deciduous) were targeted at each site. Litterfall traps were used to assess leaf damage caused by leaf‐chewing insects in 2014 and 2015. Using a standardized protocol, we assessed herbivory on 117, 918 leaves of 39 dominant tree species. Preliminary analyses suggest that insect herbivory increases with increasing latitude for deciduous broadleaf species. In particular, oak ( Quercus crispula ) and beech ( Fagus crenata ) were subject to increased insect herbivory with increasing latitude. In contrast, insect herbivory decreased with increasing latitude in evergreen broadleaf species. The latitudinal gradient of herbivory differed according to leaf type (i.e., evergreen or deciduous). This dataset offers excellent opportunities for meta‐analysis and comparative studies of herbivory among various forest types. The complete dataset for this abstract published in the Data Paper section of the journal is available in electronic format in MetaCat in JaLTER at http://db.cger.nies.go.jp/JaLTER/metacat/metacat/ERDP-2021-01.1/jalter-en . Abstract : We present the largest freely available herbivory dataset for Japan representing data collected from a network of 19 natural forest sites across the country, from subarctic to subtropical. Preliminary analyses suggest that the latitudinal gradient of herbivory differed according to leaf type; insect herbivory increased with increasing latitude in deciduous broadleaf species but decreased in evergreen broadleaf species.